"Fuelled by Dreams and Powered by Imagination": Considering Digital Technologies through the Lens of a Theology of Play. Issue 1 (March 2015) - Stoddart, Eric
<x content-type="archive" xml:space="preserve">Abstract</x> The boundaries between information and entertainment, work and leisure, and professional devices and toys are blurred. This has implications for understanding the ways in which we interact with digital devices. This article argues that these new cultural developments are not adequately addressed in existing theologies of technology and proposes that a theology of play provides an important additional critical perspective. Particular focus is placed upon Roman Catholic teachings, including the past decade's Papal messages to the World Communications Day.